Teachers’ perceptions of e-learning in Malaysian secondary schools - Cheok, Mei Lick; Wong, Su Luan; Ayub, Ahmad Fauzi; Mahmud, Rosnaini (Faculty of Education, University Malaya, 2017)
Malaysian teachers are constantly challenged with many new technologies that are believed to enable them to perform their job better. In 2013, they have been given access to an online learning space known as the FROG VLE. However, initial evidence has shown poor adoption of the e-learning. As schools are becoming increasingly disconnected from the societies of which they are a part, teachers withdrawing into their old familiar landscapes of teaching and learning can no longer be accepted. Being the implementers in the classrooms, their perceptions’ towards any innovation are important if the innovation is to be taken up seriously and to be implemented. Measures to improve present condition in order to sustain and increase e-learning uptake, can only be carried out if we know the situations and conditions teachers are in. A qualitative approach was used to identify the views and experiences of 60 secondary school teachers towards the implementation and continued use of VLEs in three secondary schools in Malaysia. This is to obtain a more nuanced explanation for the perceptions teachers’ have towards e-learning. Data was collected using an open-ended questionnaire. The results among others highlight the benefits as perceived by the teachers, the main barriers they faced and suggestions to better improve the implementation. Implications for teacher preparation, staff development efforts and education reform are proposed to overcome the challenges faced.